CONTROLLING THE USE OF MOBILE BANKING IN FINANCIAL MANAGEMENT - Berliana Ayu Safara; Dhita Berliana Tri Rahmawati Rawi (Count : Journal of Accounting, Business and Management, 2024)
Financial Financial services and financial inclusion in the digital 5.0 era are growing, especially the use of mobile banking, according to the Tempo Data and Analysis Center it is known that 74% of marketplace users shop using transfer services from mobile banking. This study aims to examine the use of mobile banking and the attitudes of individual mobile banking users in controlling personal finances. This research method uses quantitative methods of correlation and multiple linear regression analysis which requires assistance from the SPSS Statistics 27 application. The sample of this research is individual mobile banking users and the required population is 74 samples. The results of this study are that the use of mobile banking and the individual attitudes of mobile banking users towards financial management control do not affect financial management for mobile banking users. The use of mobile banking and individual attitudes in this study did not contribute much to financial management.